Postoje studentů zdravotnických oborů k seniorské populaci - Taliánová, Magda; Mikšovská, Vendula (Univerzita Pardubice, 2013)
This paper focuses on the attitudes towards the elderly among health sciences students. As the demographic data suggest, it is an issue caused mainly by year-to-year increasing number of the seniors and the need for geriatric care. The main objective of this paper was to identify respondents’ relationship to the seniors. The targets were to analyze respondents’ views on the life of today's seniors in the society, where they see advantages and disadvantages of old age, and whether they think that educational institutions dedicated to this issue devote enough time to this problem. The survey included 142 questionnaires completed by the students of health sciences in the Pardubice region. The resulting data were evaluated with the help of chi-square test for independence (significance level 0.05) and relative frequency.
Attitudes of health studies students towards the elderly
Keywords: seniors; society; intergenerational problem; prejudices; ageism